Africanisation of Psychology: Identities and Continents - Dawes, Andy (PINS-Psychology in Society, 2026)
The psychologies of North America and Europe have long dominated African academies. The relevance of this knowledge for people of African origin, has been challenged in arguments for the Africanisation of the discipline. A common argument is that an understanding of African epistemologies is necessary for the development of psychological knowledge appropriate to the continent. Inherent in this position, but usually unrecognised, is a challenge to the external validity of knowledge claims developed outside the conditions which construct mentality in Africa. Also evident is a tendency to totalise African experience and mentality. Despite some debate, the idea of Africanisation in psychology has not been systematically developed. The current paper attempts to take the discussion forward. Following a discussion of ways in which the Africanisation of the discipline has been considered, I suggest that is necessary to distinguish between the Africanisation of psychological knowtedge, and the appropriate application of modern psychological theory and research in African contexts. The former suggests a challenge to the professional psychologies of Europe and the United States, and in some versions, it may imply the adoption of the traditional ethnopsychologies of Africa. The latter position leaves these claims largely intact while developing eco-culturally sensitive interventions. This contribution argues that an African psychology should draw on both local and external knowledge systems. But in wishing to call itself a psychology it needs to be guided by the conventions for psychological activity which exist in the various corners of the discipline.